IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH MELALUI KEGIATAN PEMBIASAAN DAN KETELADANAN - Aidah Sari (Tarbawi, 2017)
The purpose of this study is 1) To know the teacher’s understanding of character education in MI Raudlatul Aulad, 2) To describe the implementation of character education through habituation and exemplary activities, 3) Know what obstacles are faced in the implementation of character education through habituation and exemplary activities. is qualitative research, informants of this study are principals and teachers. Data collection techniques using observation, documentation and interview techniques. Data were analyzed through steps of data reduction and conclusion. The technique of checking the validity of the data is done by source triangulation and methods. The results of this study are the process of implementing character education through habituation and exemplary activities, and obstacles faced in the process of implementing character education Keywords. Character education, habituation, nonsuch.